ВПЛИВ ГЛОБАЛІЗАЦІЇ СВІТОВОГО РИНКУ ПРАЦІ НА ЕФЕКТИВНІСТЬ ВИКОРИСТАННЯ ТРУДОВОГО ПОТЕНЦІАЛУ УКРАЇНИ (International Journal of Innovative Technologies in Economy, 2018)
In the article the main trends of use labor potential of Ukraine and its impact on economic processes nationwide level.Delineated basic principles of participation and factors of act the domestic workforce in the global labor market in environments of increased globalization. Investigated the potential and structure of migration processes and the directions of state regulation in accordance with unified international standards. Analyzed the relationship between open labor markets countries and internal control of unemployment. Revealed links between the levels of development of the economy and the degree of activity the domestic labor potential in the system of international relations labor resource in globalized world. Outlined promising directions of the state policy in the field of labor markets in terms of integration processes as a regulating factor the social and economic crisis of the country.